Older Adults' Perceptions of Sedentary Behavior: A Systematic Review and Thematic Synthesis of Qualitative Studies. (31st October 2019) - Compernolle, Sofie; De Cocker, Katrien; Cardon, Greet; De Bourdeaudhuij, Ilse; Van Dyck, Delfien
Abstract: Background and Objectives: Reducing sedentary behavior contributes to healthy aging. In order to develop sedentary behavior interventions, insight is needed into older adults' perceptions of (reducing) sedentary behavior. Therefore, this systematic review aims to synthesize qualitative evidence of older adults' perceptions towards (a) the concept of sedentary behavior, (b) barriers and facilitators of sedentary behavior, and (c) solutions and strategies to reduce sedentary behavior. Research Design and Methods: A systematic search was conducted in four electronic databases. Inclusion criteria comprised qualitative and mixed-methods studies investigating the perceptions of older adults (mean age: ≥60 years) towards (reducing) sedentary behavior. Quality of the included studies was rated using the Critical Appraisal Skills Programme (CASP) Qualitative Checklist. Relevant data on older adults' perceptions were extracted and imported into NVivo. Two independent reviewers analyzed the data by means of thematic synthesis (line-by-line coding, constructing descriptive (sub)themes, developing analytical themes). Results: Fifteen studies were included. Four analytical themes were developed to be considered when aiming to reduce sedentary behavior in older adults: the lack of knowledge on/awareness of sedentary behavior, the habitual nature of sedentary behavior, the importance of enjoyment and convenience, and the key role of aging. Discussion and Implications: The reduction of older adults' sedentary behavior will likely be challenging as sedentary behavior seems to be firmly incorporated into older adults' daily routines, and strongly linked with positive reinforcement. Both aspects deserve thoughtful attention by intervention developers and health care professionals who aim to promote healthy aging by reducing sedentary behavior.